(untitled) (International Journal of Engineering and Computer Science, 2014)
Energy is very much important input in all sectors of any country’s economy. The standard of living of any country can be directly related to per capita energy consumption. The ever increasing population on the world and increased standard of living of human being has no doubt put a tremendous pressure on Earth’s Resources. In this research paper, Study of Energy Conservation and Energy Audit in industry. It is carried out and very effectively tried to make systematic approach for the same. It is studied that results of energy conservation and energy audit point out possibilities of energy saving, by simple housekeeping measures as well as improved techniques, better instrumentation and more efficient machinery. A careful day to day monitoring of specific energy consumption can help in saving wastage of energy and raw materials.